FAKTOR? FAKTOR YANG MEMPENGARUHI MINAT MENGIKUTI PROGRAM PENDIDIKAN BREVET PAJAK DI STIE PERBANAS SURABAYA - Bayu Sarjono (The Indonesian Accounting Review, 2011)
Tax certification of Education Progam is estabilishedby STIE Perbanas Surabaya in theform of training for university students or external party. At this moment, the demand for a tax occountant or tax consultant keeps on increasing, moreover when the there is Law No.28 Year 2007 about Taxation General Stipulation. This condition has the effect of effortperformed by DJP in order to increase state revenue. Universities are expected producethe graduates with enough knowledge and skill of taxation. Tax certification training isexpected to support the graduates' competency. This research tries to find out what factorsthose influence university students to be interested in joining the tax ceitification program atSTIE Perbanas Surabaya. This research is quantitative research using multiple regressiontest. The respondents in this research consist of all members of tax certificationof Level Iand Level II. The data were collected by spreading direct questionnaires and performingFocus Group Discussion. The result of statistic test shows that only economic motivationvariable has significant infiuence towards the interest to join tax certification program.They explain that they join the tax certification program in order to get ligal document thatcan be used to apply for a job and also because they think that they don iow any intentionto become tax accountont or tax consultant.